Pengaruh Brain Gym Therapy terhadap Tingkat Depresi Pasien Diabetes Melitus Tipe 2 - Wahyuliniya, Anak Agung Istri; Harini, I Gusti Ayu; Candra, I Wayan; Lestari, Agus Sri (Jurnal Gema Keperawatan, 2024)
Diabetes melitus (DM) is a serious chronic disease. DM is a major cause of many diseases, such as blindness, heart disease, and kidney failure. The incidence of DM in Indonesia is 2.8%, and Bali Province is 1,33%. DM patients can experience depression due to the need for long-term treatment to avoid complications. The purpose of this study was to determine the effect of brain gym therapy on depression levels in patients with type 2 DM. Pre experimental research design with One-group pre-post test design. The research sample was DM patients who experienced depression. The sampling technique used was purposive sampling. This research instrument uses the beck depression inventory II questionnaire. The statistical test used is the Wilcoxon test. Measurement of depression levels in DM patients was  measured twice, namely before and after being given brain gym. The level of depression in research subjects before being given therapy in the moderate depression category, as many as 10 people (55,6%). The level of depression in the research subjects after being given therapy in the mild depression category, as many as 15 people (83,3%). Based on the results of the Wilcoxon test, the p value= 0,008 was obtained.  The p value 0,05 indicates that there is an effect of brain gym therapy on depression in DM patients. The conclusion of this study is that brain gym reduces the level of depression in patients with type 2 DM.